Boiling Heat Transfer to Turbulent Liquid Films - Dernedde, Edgar (My University, 1966)
Benzene and water films were passed over an inclined, hot copper plate. The boiling heat transfer to the turbulent liquid films has been measured with local heat-flux meters. These meters have been adopted from a design suggested by Gardon (G10), and could be used to measure boiling heat fluxes with an accuracy of about -20,000 BTU/hr.sq.ft. The results indicate that the heat transfer to the liquid films compares well with that of forced convection subcooled boiling.
During boiling the liquid film is destroyed by the growing vapour bubbles and by the separation of the liquid from the hot plate. The break-up of the liquid films has been investigated with high-speed photography but an analysis of the hydrodynamics of this break-up has not been made.
Keywords: chemical engineering; heat-flux meter; boiling heat transfer; turbulent liquid film; benzene; water; copper plate